2011
DOI: 10.1371/journal.pone.0029553
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Immunization of the Combined Lipooligosaccharide Conjugates Protects Mice from the Challenges with Three Serotypes of Moraxella catarrhalis

Abstract: BackgroundThere are no licensed vaccines available against Moraxella catarrhalis, a significant human respiratory pathogen. Lipooligosaccharide (LOS) based conjugate vaccines derived from individual serotype M. catarrhalis only showed partial protection coverage. A vaccine combining LOS conjugates of two or three serotypes might provide a broader protection.MethodsMice were immunized intranasally with the combined conjugates consisting of LOS from serotype A and B or serotype A, B, and C followed by challenge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Current evidence indicates that these common microbiota changes present in allergic respiratory diseases are associated with these immune disorders, which may serve as potential therapeutic targets for allergic respiratory diseases. [76][77][78] The relationship between covariant microbiota and immune inflammation is summarized in Figure 4, which shows that the commonly changed microbiota can be divided into three categories according to their relationship with immune inflammation. Bacteria that promote immune inflammation and can increase IgE production.…”
Section: The Association Between Changed Microbiota and Immune Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Current evidence indicates that these common microbiota changes present in allergic respiratory diseases are associated with these immune disorders, which may serve as potential therapeutic targets for allergic respiratory diseases. [76][77][78] The relationship between covariant microbiota and immune inflammation is summarized in Figure 4, which shows that the commonly changed microbiota can be divided into three categories according to their relationship with immune inflammation. Bacteria that promote immune inflammation and can increase IgE production.…”
Section: The Association Between Changed Microbiota and Immune Disordersmentioning
confidence: 99%
“…aureus , Haemophilus, andPseudomonas , seem to trigger Th1/Th2, Treg/Th17 imbalance and release of IgE, although they are sometimes positively correlated with anti-inflammatory cytokines. [76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94] The other genera including Neisseria and Streptococcus are in a positive relationship with IgE levels, but the connection with other immune cells is ambiguous. [95][96][97][98][99][100][101][102][103][104][105][106][107][108][109] The second category of bacteria mainly found in the intestine is charactered by the increase of antiinflammatory cytokines and decrease of pro-inflammatory cytokines, which has the capability to modulate immune dysregulation and build a defensive line against inflammation.…”
Section: The Association Between Changed Microbiota and Immune Disordersmentioning
confidence: 99%
“…Studies using animal models and the mucosal immunization route have demonstrated that immunization was able to significantly enhance clearance of each bacterium from the middle ear when subsequently challenged with live bacteria (Cripps and Kyd, 2007). Inclusion of multiple serotypes in an experimental LOS-based vaccine against M. catarrhalis elicited humoral and cellular immune protection against most strains within a mouse model (Ren et al, 2011). For humans, the disappointing outcomes of current polysaccharide conjugate vaccines on AOM, despite good systemic antibody responses, may be several: serotype replacement following vaccination by non-vaccine serotypes or other bacterial otopathogens; different causative S. pneumoniae serotypes from those that cause invasive disease; suboptimal antibody responses following immunization to some serotypes; and the lack of induction of mucosal immune responses in the middle ear following systemic immunization (Cripps and Otczyk, 2006).…”
Section: Mucosal Immunization To Prevent Middle Ear Infectionmentioning
confidence: 99%
“…Further investigation on protective effects is required to assess the mutant LOS-based conjugate as a vaccine antigen. Another approach has been attempted by combining the dLOS–protein conjugates from all three serotypes of M. catarrhalis as a vaccine antigen [96]. Intranasal immunization of the combined dLOS–protein conjugates induces significant humoral and cell-mediated immune responses, which enhance the clearance of six strains of all three serotypes of M. catarrhalis from the lungs of mice challenged with the bacteria [96].…”
Section: M Catarrhalis Vaccine Candidatesmentioning
confidence: 99%